Gynandromorphism in Xylocopinae Bees (Hymenoptera: Apidae): description of four new cases - Lucia, Mariano; Alvarez, Leopoldo J.; Abrahamovich, Alberto H. (Zootaxa, 2012)
Four new gynandromorph Xylocopinae bees from Argentina are described and illustrated; one specimen of Xylocopasplendidula Latreille and three of Ceratina rupestris Holmberg. All specimens are mosaic gynandromorphs as they display mixed female-male characters in different parts of the body.